Fermentation Time and Environmental Conditions Changes Nutritional Composition of Fermented Rice and Wheat Bran - Debi, Momota Rani; Islam, Khan Md. Shaiful; Saha, Biplob Kumar (Indian Journal of Animal Nutrition, 2025)
The utilization of rice bran (RB) and wheat bran (WB) in broiler is limited due to low protein and high fiber content. Therefore, this study was conducted to increase the nutritive value of these by-products through fermentation with rumen liquor. Rumen microbes are very sensitive to pH for their proper functioning. To achieve these goals, precise fermentation of RB and WB using rumen liquor was conducted in a different environmental condition. Environment 1: fermentation in a hot plate with magnetic stirrer at 39°C; Environment 2: fermentation in an incubator at 39°C; Environment 3: fermentation in a room temperature. The fermentation was performed for different periods from 3 to 72 hours with 3 replications (n=3). The fermentation was initiated with pH 7 by adding some buffer substances. Results showed that pH changed significantly (p<0.05) in a different environment as well as with duration of fermentation. After some hours, pH reduced to a level that is harmful for fiber degrading microbes. For nutritional composition, better results were obtained in the case of environment 1 compared to others explaining that this environment was more appropriate for rumen microbes for their proper function. It can be concluded from the results that pH is very sensitive with time of fermentation as well as with different environmental conditions. However, further research is required to verify that the addition of supplementary buffer during fermentation might improve or stable the pH of the fermentation which might produce better fermented product.